2021
DOI: 10.3389/fmars.2021.699521
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap

Abstract: The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Clear plastics seemed to be due to the breakdown process where the plastic wastes were exposed to the UV radiation and mechanical stress caused by the wave movement at the beach (Lechthaler et al, 2020). Duncan et al (2021) reported that clear (36 %), white (36 %), green (16 %), and blue (16 %) were the dominant colors found in turtle stomachs from the Pacific Ocean regions, with the most common polymers identified were PE (58 %) and PP (20.2 %). These ingested plastics were usually found as hard fragments (52 %), filaments (52 %), and plastic sheet (38 %) with sizes from about 5 mm to approximately 220 mm.…”
Section: Macroplasticsmentioning
confidence: 99%
“…Clear plastics seemed to be due to the breakdown process where the plastic wastes were exposed to the UV radiation and mechanical stress caused by the wave movement at the beach (Lechthaler et al, 2020). Duncan et al (2021) reported that clear (36 %), white (36 %), green (16 %), and blue (16 %) were the dominant colors found in turtle stomachs from the Pacific Ocean regions, with the most common polymers identified were PE (58 %) and PP (20.2 %). These ingested plastics were usually found as hard fragments (52 %), filaments (52 %), and plastic sheet (38 %) with sizes from about 5 mm to approximately 220 mm.…”
Section: Macroplasticsmentioning
confidence: 99%
“…Plastic reaches the turtles through random feeding, as turtles sometimes do not differentiate between food and plastic, especially that plastic, which is very similar to turtle food [21]. There are two ways for plastic to reach sea turtles direct and indirect road, direct ingestion of plastic parts and bags where this is observed in all types of sea turtles Figure 2 [22,23]. Ingestion sometimes occurs directly when plastic pieces are mixed with the food of choice for these sea turtles, for example, a study found that small green turtles (Chelonia mydas) inside their digestive system contain pieces of plastic because they feed on a type of macro algae that had plastic pieces attached to it Di Beneditto and Awabdi [24].…”
Section: Sea Turtlesmentioning
confidence: 99%
“…WWF Malaysia (2020) discovered that if a turtle ate just one piece of plastic, it had a 22% chance of dying. The ingestion of plastics by sea turtles is found in all species (Duncan et al 2021). The plastics' sharp edges can damage their internal organs and can cause intestinal blockages, making them unable to feed which leading to starvation.…”
Section: Introductionmentioning
confidence: 99%